Letter - Winstanley, E.
032-0059-001 TELEGRAPHIC ADDRESS: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. CABLE CODES: A.B.C. 6TH AND 7TH EDITIONS; WESTERN UNION 8 LETTER; BENTLEY COMPLETE PHRASE; BENTLEY SECOND PHRASE; A.1. MARCONI, AND PRIVATE. Our Reference: Export.2967.ST/RN. Your Reference: 10th May, 1939. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sir, Further to our telephonic conversation with you on Monday, we have to inform you that, owing to a slight mishap to the C.W.S. PROGRESS in the Mersey, we will have no sailing from Garston to Rouen until June 1st, but if this date is suitable we shall be glad to arrange all shipping formalities on your behalf. Yours faithfully, E. Winstanley, Export Department. E.A.B. 292/946/32/59